Integration of sustainability, stakeholder and process approaches for sustainable offshore wind farm decommissioning. (September 2021) - Spielmann, Vanessa; Brey, Thomas; Dannheim, Jennifer; Vajhøj, Jesper; Ebojie, Mandy; Klein, Johanna; Eckardt, Silke
Abstract: At the end of their operational life offshore wind farms need to be decommissioned. Up to date only few offshore wind farms were decommissioned, so there is a lack of experience and knowledge and decommissioning processes are largely unknown. Also, relevant stakeholders that might interfere with the decommissioning project are poorly investigated. As source of renewable energy, offshore wind farm decommissioning should be sustainable. This paper outlines a practical concept of integrating the three approaches for a sustainable decommissioning of offshore wind farms. It comprises a stakeholder approach, where relevant stakeholders are identified and analysed, a sustainability approach, in which objectives for sustainable offshore wind farm decommissioning are defined, and a process approach, including the selection, documentation and parametrization of decommissioning processes. The theoretical concept of the integration of the three approaches is outlined first. Thereafter the concept is applied on a case study of offshore wind farm decommissioning. Highlights: First interdisciplinary research for sustainable offshore wind farm decommissioning. Our concept integrates sustainability, stakeholder and process approaches. We evaluate economic, environmental and social aspects of decommissioning. We consider all relevant stakeholders of offshore wind farm decommissioning. We analyse and assess the entire end-of-life process of offshore wind farms.